The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1678-992x-2016-0079
|View full text |Cite
|
Sign up to set email alerts
|

Universal tail sequence-SSR applied to molecular characterization of tropical maize hybrids

Abstract: The development of efficient and low-cost genotyping methods is essential to precise genetic characterization of cultivars. Here, we present a system based on fluorescently labeled universal tail sequence primers (UTSP) to resolve microsatellite (SSR) markers as an alternative for molecular fingerprinting of maize. A set of 20 SSRs using the UTSP presented an average polymorphic information content of 0.84, which provided a probability of random identity ranging from 10 −7 to 10 −14, and a minimum exclusion po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Kozhukhova and Sivolap (2004) differentiated 40 unique molecular patterns of 40 maize genotypes with ten polymorphic SSR loci. In another study, 20 microsatellites revealed unique allelic combinations for 48 commercial maize single-cross hybrids, with a probability of identity ranging from 10 − 14 to 10 − 7 (Ribeiro et al, 2017).…”
Section: Locusmentioning
confidence: 95%
“…Kozhukhova and Sivolap (2004) differentiated 40 unique molecular patterns of 40 maize genotypes with ten polymorphic SSR loci. In another study, 20 microsatellites revealed unique allelic combinations for 48 commercial maize single-cross hybrids, with a probability of identity ranging from 10 − 14 to 10 − 7 (Ribeiro et al, 2017).…”
Section: Locusmentioning
confidence: 95%
“…which indicates the power to unambiguously identify a given individual or subpopulation among all others in the set, using the 16 SSR markers described in this study (Ribeiro et al 2017).…”
Section: Identity Estimation Abilitymentioning
confidence: 97%